Aceh’s Democratic Landscape: Exploring the Role and Impact of Local Political Parties - Yuriadi Yuriadi; Probojati Bayu Herlambang; Naura Darrin Hasan (CV. Era Digital Nusantara, 2023)
Abstract: After issuing Law No. 18/2001 on Special Autonomy for the Special Province of Aceh. The central government has given extensive concessions to Aceh Province by delegating various authorities, including forming local Aceh political parties. Local political parties are political organizations formed voluntarily based on similarities of will and ideals to fight for the interests of the community, nation, and state through the election of members of the Dewan Perwakilan Rakyat Aceh, Governor, Regent, and Mayor. the existence of local political parties is considered effective in carrying out their roles and functions, especially in implementing the party system in the special autonomy region of Indonesia. Purpose: This study aims to identify and comprehend the role played by Aceh’s local political parties in the local-level implementation of democratization. Design/Methodology/Approach: This research method uses a legal research method with a conceptual and statutory approach. Findings: The results of the study show that the existence of Acehnese local parties can provide political advantages for interest groups to seize power, with the presence of local parties given way as a political vehicle to mobilize power in its government, both in the legislature and the executive. The existence of local parties can embrace all the aspirations of the Acehnese people more specifically than national parties. For this reason, local parties can support the implementation of special autonomy in Aceh. Originality/Value: There are many studies on local parties in Aceh, but this research explores the existence of local parties in implementing local democracy in Aceh.